Doxorubicin Hydrochloride Loaded Polyanhydride Nanoformulations and Cytotoxicity - Sreeharsha, Nagaraja; Hiremath, Jagadeesh G; R, Prashanth Kumar; Meravanige, Girish; Khan, Saleemulla; Karnati, Ranjith Kumar; Attimarad, Mahesh; Al-Dhubiab, Bandar; Nair, Anroop Balachandran; Venugopala, Katharigatta Narayanaswamy (Indian Journal of Pharmaceutical Education and Research, 2021)
This study aimed to evaluate DOX∙HCl loaded P(DLLA-CO:60:40) nanoformulations with a copolymer of F127 as a potential drug delivery system for cancer. DOX ∙ HCl was encapsulated in nanoformulations of Poly DL-lactic acid co castor oil 60:40, P(DLLACO: 60:40) polymer with the copolymer/stabilizer Pluronic® F127. The mean diameter of the cylindrical rod shape of the nanoformulation particles was 248±2.4-260±3.2 nm with an acceptable poly dispersibility of 0.29- 0.33 and a smooth surface as visualized by DSC, SEM and XRD displayed that DOX∙HCl was present as an disordered crystalline or amorphous state in the nanoformulations. The nanoformulations showed a steady pattern of drug discharge for 24 hrs. F-3 and F-4 formulations had IC50 values of 3.2±0.03 and 1.98±0.08 mcg/ml while the free drug inhibition concentration of IC50 was 2.2 mcg/ml. The drug-loaded nanoformulations showed significant cytotoxic effects on MCF-7 breast cancer cell lines.
Keywords: Doxorubicin hydrochloride; MCF-7 breast cancer cell lines; Nanoformulations; Drug delivery